New Frontiers in Social Innovation Research - Nicholls, Alex; Simon, Julie; Gabriel, Madeleine (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book is open access under a CC BY license. Interest in social innovation continues to rise, from governments setting up social innovation 'labs' to large corporations developing social innovation strategies. Yet theory lags behind practice, and this hampers our ability to understand social innovation and make the most of its potential. This collection brings together work by leading social innovation researchers globally, exploring the practice and process of researching social innovation, its nature and effects. Combining theoretical chapters and empirical studies, it shows how social innovation is blurring traditional boundaries between the market, the state and civil society, thereby developing new forms of services, relationships and collaborations. It takes a critical perspective, analyzing potential downsides of social innovation that often remain unexplored or are glossed over, yet concludes with a powerful vision of the potential for social innovation to transform society. It aims to be a valuable resource for students and researchers, as well as policymakers and others supporting and leading social innovation.